1998
DOI: 10.1111/j.1651-2227.1998.tb01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Speech and language skills in children who required neonatal intensive care. I. Spontaneous speech at 6.5 years of age

Abstract: Spontaneous speech at age 6.5 years was studied separately in a follow‐up of speech and language skills in a regional cohort of 284 children requiring neonatal intensive care and in 40 controls. Eight aspects of spontaneous speech were evaluated in a conversation: A1, information; A2, speech motor function; A3, sound pattern; A4, word finding; A5, word selection; A6, grammar; A7, interaction; and A8, motivation. The children were grouped by gestational age. Most children had well developed spontaneous speech. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Excluded studies that presented data relating to the wider group of infants born between 32 and 36 weeks' gestation have been detailed for reference (see Table 2). [27][28][29][30][31][32][33][34][35] For example, Darlow et al 27 considered 2-year outcomes in an entire preterm cohort, including a subgroup of infants who were born at 33 to 36 weeks' gestation; although excluded on the basis of gestational age, this study provided useful comparative data for the wider group.…”
Section: Included Studiesmentioning
confidence: 99%
“…Excluded studies that presented data relating to the wider group of infants born between 32 and 36 weeks' gestation have been detailed for reference (see Table 2). [27][28][29][30][31][32][33][34][35] For example, Darlow et al 27 considered 2-year outcomes in an entire preterm cohort, including a subgroup of infants who were born at 33 to 36 weeks' gestation; although excluded on the basis of gestational age, this study provided useful comparative data for the wider group.…”
Section: Included Studiesmentioning
confidence: 99%
“…Jennische and Sedin found that children who received intensive neonatal care had subsequent problems with both spontaneous speech and measures in language tests 25, 26. Small for gestational age in particular was an indicator of subsequent problems.…”
Section: Discussionmentioning
confidence: 98%
“…Often, infants either born prematurely or possessing congenital diseases need temporary nutritional support via tube feeding. Frequently, these infants display feeding impairments and motor speech delays (Bier et al, 1993; Jennische and Sedin, 1998,1999; Hawdon et al, 2000; Dodrill et al, 2004). It is possible in these cases that impaired oral feeding is due to hypersensitivity in the oropharyngeal region.…”
Section: Introductionmentioning
confidence: 99%